Enhancing flotation removal of unburned carbon from fly ash by coal tar-based collector: Experiment and simulation. (15th January 2023) - Zheng, Kanghao; Zhang, Wenjun; Li, Yijiang; Ping, An; Wu, Feng; Xie, Guangyuan; Xia, Wencheng
Highlights: A coal tar-based (CTB) collector is introduced in unburned carbon (UC) flotation. The CTB collector increases the content of hydrophobic groups on the UC surface. The adsorption characteristics of CTB collector on the UC surface are revealed. The CTB collector shortens the liquid film thinning time on the UC surface. Abstract: The unburned carbon (UC) in fly ash is a vital parameter that governs the further utilization of fly ash in mortar and concrete industry. Flotation is an effective methodology for removing the UC from fly ash. However, the specific physicochemical properties of the UC particle surface make them difficult to float. In this study, a coal tar-based (CTB) collector was used to remove the UC from fly ash through flotation process. The adsorption mechanism of the CTB collector and diesel on the UC particle surface was characterized by scanning electron microscopy-energy dispersive spectrometry (SEM-EDS), fourier-transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), molecular dynamics (MD) simulation, and induction time tests. The levels of oxygen-containing functional groups and aromatic ring compounds present in the CTB collector were considerably higher than those in diesel. The oxygen-containing functional group contents on the untreated UC surface, the diesel-treated UC surface, and the CTB collector-treated UC surface decreased in that order. The MD simulation results indicated that the aromatic compounds (dibenzofuran and naphthalene, etc.) in the CTB collector interacted strongly and adsorbed at deep locations with the UC surface compared to the alkanes (dodecane, diesel, etc.). The alkanes are indispensable as the collector in the fly ash flotation process and synergize with aromatic compounds to improve the mobility of water molecules on the UC surface. The CTB collector significantly enhanced the floatability of the UC particle and hence improved the flotation removal of UC from fly ash.